2014
DOI: 10.5455/medarh.2014.68.324-328
|View full text |Cite
|
Sign up to set email alerts
|

Correlation Between Blood Lead Level and Hemoglobin Level in Mitrovica Children

Abstract: Introduction:Lead toxicity is a serious health threat, especially in developing countries due to environmental pollution. It was thus aimed to investigate correlation between blood lead level and concentration level of hemoglobin in the blood of children involved in research.Material and methods:The research included 250 children of which 31(12.4%) kindergarten children, 166 (66.4%) of primary school pupils in Mitrovica and 53(21.2%) of primary school pupils in Shtime as control group. From the 250 children in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
12
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(15 citation statements)
references
References 19 publications
2
12
1
Order By: Relevance
“…Blood lead concentrations, average levels 23.6 AE 15.9 μg/dL À , in the children in our study were 3 to 12 times higher than the current average (1.9 μg/dL) of children (ages 1-5 years) in the United States. 23 In contrary, various scientific research, 13,[24][25][26] that calculated BLL in children in developing countries, also had similar results to ours.…”
Section: Discussionsupporting
confidence: 85%
“…Blood lead concentrations, average levels 23.6 AE 15.9 μg/dL À , in the children in our study were 3 to 12 times higher than the current average (1.9 μg/dL) of children (ages 1-5 years) in the United States. 23 In contrary, various scientific research, 13,[24][25][26] that calculated BLL in children in developing countries, also had similar results to ours.…”
Section: Discussionsupporting
confidence: 85%
“…Whether lead can inhibit Hb synthesis is closely related to the child's lead load level. Research by Chen and Kutllovci-Zogaj showed that blood lead could interfere with Hb synthesis [8,9]. The United States Centers for Disease Control (CDC) has recommended that BLL can be used for the assessment of the lead load in the body and the degree of lead poisoning.…”
Section: Comparison Of In Uencing Factors Of Anaemia Among Children Imentioning
confidence: 99%
“…Blood lead and blood cadmium may interact with Hb [8]. Kutllovci-Zogaj et al used Spearman correlation analysis to analyse the relationship between BLL and Hb level in children in Mitrovica and found that there was a moderate correlation between BLL and Hb level [9]. However, previous studies did not exclude the in uence of common nutritional and genetic factors in the impact of lead exposure on Hb.…”
Section: Introductionmentioning
confidence: 99%
“…Blood lead and blood cadmium may interact with Hb (Chen et al 2015 ). Kutllovci-Zogaj et al used Spearman correlation analysis to analyse the relationship between BLL and Hb level in children in Mitrovica and found that there was a moderate correlation between BLL and Hb level (Kutllovci-Zogaj et al 2014 ). However, previous studies did not exclude the influence of common nutritional and genetic factors in the impact of lead exposure on Hb.…”
Section: Introductionmentioning
confidence: 99%